Decolonial Approaches to Latin American Literatures and Cultures
XXXVI, 235 p. 4 illus., 3 illus. in color.
Keywords: Decolonial Approaches to Latin American Literatures and Cultures engages and problematizes concepts such as “decolonial” and “coloniality” to question methodologies in literary and cultural scholarship. While the eleven contributions produce diverse approaches to literary and cultural texts ranging from Pre-Columbian to contemporary works, there is a collective questioning of the very idea of “Latin America,” what “Latin American” contains or leaves out, and the various practices and locations constituting Latinamericanism. This transdisciplinary study aims to open an evolving corpus of decolonial scholarship, providing a unique entry point into the literature and material culture produced from precolonial to contemporary times.